Comparative evaluation of clinical glycemic control markers treated with imeglimin and its effect on erythrocytes in patients with type 2 diabetes mellitus: study protocol of a single-arm, open-label, prospective, exploratory trial - Osonoi, Takeshi; Shirabe, Shinichiro; Saito, Miyoko; Hosoya, Mitsuru; Douguchi, Satako; Ofuchi, Kensuke; Katoh, Makoto (Frontiers in Pharmacology, 2023)
Background: Imeglimin is a novel type 2 diabetes (T2D) drug that is expected to improve mitochondrial function. In its phase 3 clinical trials in Japanese patients with T2D, the hemoglobin A1c (HbA1c) decrease following imeglimin administration was slow, reaching a plateau after 20–24 weeks of treatment. In general, the erythrocyte lifespan may be a factor when HbA1c shows an abnormal value. Therefore, this study will comparatively evaluate HbA1c and other markers of glycemic control in patients with T2D after imeglimin administration and also examine the effects of imeglimin on erythrocytes. Methods: This single-arm, open-label, prospective, exploratory study is designed to evaluate the divergence between HbA1c and glycoalbumin (GA) or 1,5-anhydroglucitol (1,5-AG) and the glycemic reduction rate in 30 patients with T2D with inadequate glycemic control when imeglimin 2,000 mg is administered for six months. In addition, we will examine the effect on erythrocytes, the presumed cause of this divergence. We will measure sustained glycemic variability using flash glucose monitoring and examine the relationship between changes in these indices and HbA1c. Moreover, because prolonged erythrocyte lifespan is a possible cause of falsely high HbA1c levels, erythrocyte lifespan, erythrocyte deformability, and hemoglobin concentration will be evaluated as effects of imeglimin on erythrocytes. Furthermore, if imeglimin has an ameliorative effect on erythrocyte deformability, it may improve peripheral arterial disease; thus, we will also evaluate the toe-brachial pressure index, a measure of this effect. Discussion: In this study, if imeglimin administration results in diverging rates of hypoglycemic effect between HbA1c and GA or 1,5-AG and prolongs erythrocyte lifespan, GA and 1,5-AG, rather than HbA1c, will be considered appropriate measures of the hypoglycemic effect in the early stages of imeglimin administration. If imeglimin improves erythrocyte deformability, it may also be a new treatment strategy for peripheral arterial disease, a chronic complication of T2D. Ethics and dissemination: The study protocol was scientifically and ethically reviewed and approved by the Certified Clinical Research Review Board of Toho University (approval number: THU22002). The study protocol was registered in the Japan Registry of Clinical Trials (jRCT) in December 2022 (jRCTs031220489)